Reproducibility of a silicone-based test food to masticatory performance evaluation by different sieve methods - Alfonso Sánchez-Ayala; Larissa Soares Reis Vilanova; Marina Abrantes Costa; Arcelino Farias-Neto (Brazilian Oral Research, 2014)
The aim of this study was to evaluate the reproducibility of the condensation silicone Optosil Comfort® as an artificial test food for masticatory performance evaluation. Twenty dentate subjects with mean age of 23.3 ± 0.7 years were selected. Masticatory performance was evaluated using the simple (MPI), the double (IME) and the multiple sieve methods. Trials were carried out five times by three examiners: three times by the first, and once by the second and third examiners. Friedman’s test was used to find the differences among time trials. Reproducibility was determined by the intra-class correlation (ICC) test (α = 0.05). No differences among time trials were found, except for MPI-4 mm (p = 0.022) from the first examiner results. The intra-examiner reproducibility (ICC) of almost all data was high (ICC ≥ 0.92, p < 0.001), being moderate only for MPI-0.50 mm (ICC = 0.89, p < 0.001). The inter-examiner reproducibility was high (ICC > 0.93, p < 0.001) for all results. For the multiple sieve method, the average mean of absolute difference from repeated measurements were lower than 1 mm. This trend was observed only from MPI-0.50 to MPI-1.4 for the single sieve method, and from IME-0.71/0.50 to IME-1.40/1.00 for the double sieve method. The results suggest that regardless of the method used, the reproducibility of Optosil Comfort® is high.